Strategic alliances and green innovation bubbles: drivers, distortions, and environmental consequences - Wang, Hongda; Xiang, Jingyi; Xie, Tianwei (Frontiers in Public Health, 2025)
IntroductionAmid global ecological crises and China’s “dual-carbon” goals, green innovation has emerged as a crucial strategy for sustainable development. However, the phenomenon of “green innovation bubbles”—where innovation input and actual environmental output are misaligned—raises concerns about the effectiveness of such efforts. This study explores how corporate strategic alliances influence the formation of green innovation bubbles and examines the moderating role of new-quality productivity.MethodsDrawing on resource dependence theory and signaling theory, we constructed a panel dataset of 2,346 Chinese A-share listed companies from 2015 to 2022. We developed a Green Patent Bubble Index (GPBI) based on green patent growth, citation frequency, and structural quality. Regression analyses were conducted to assess the direct, moderating, and mediating effects of strategic alliances, new-quality productivity, information asymmetry, and policy resource acquisition.ResultsFindings indicate that strategic alliances significantly contribute to green innovation bubbles. Horizontal and diversification alliances amplify this effect, whereas vertical alliances mitigate it. New-quality productivity negatively moderates the alliance-bubble relationship, meaning firms with stronger innovation capacities are less prone to bubbles. Information asymmetry and policy resource acquisition both serve as significant mediators in this process. The bubble effect is more pronounced in state-owned enterprises and in regions with weaker environmental regulations.DiscussionThese findings reveal the dual nature of strategic alliances—serving both substantive and symbolic purposes—and highlight the risks of misallocated innovation under policy-driven incentives. The results underscore the importance of firm-level absorptive capacity and regulatory strength in curbing superficial green innovation. This research provides valuable insights for policymakers, businesses, and investors seeking to promote authentic and effective green innovation aligned with environmental and public health objectives.